IDENTIFIKASI ENTEROBACTERIACEAE PADA SUSU KAMBING PERANAKAN ETTAWAH (PE) DI PETERNAKAN SAHABAT ALAM SEJATI, KALASAN, SLEMAN - , DIAN MEIDIDEWI NURAINI; , Dr. drh.Agnesia Endang Tri Hastuti Wahyuni, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
number of consumer keep increasing lately. Goat farm prospect is still growing in Indonesia following the number of consumer. The development of goat farm in Yogyakarta is high enough. One of the success farm in Yogyakarta is Peternakan âSahabat Alam Sejatiâ in Kalasan, Sleman. The principal problem in this farm is mastitis. Most of mastitis on goat is caused by infection of bacteria including Enterobacteriaceae family. This study aims to identify Enterobacteriaceae in goatâs milk from Peternakan âSahabat Alam Sejatiâ. This study used 40 samples from 20 goats. Samples were tested by IPB-1 reagent to determine the mastitis status and inoculated on Mac Conkey agar (MCA). The colonies from MCA were stained by Gram stain to determine cell morphology. The colonies from MCA were isolated on eosin methylen blue (EMB), triple sugar iron (TSI) and were tested by indol, methyl red, voges proskauer, citrat (IMViC), glucosa, sucrose, lactose broth, and urea agar. The result of mastitis test showed 37 samples (92,5%) were subclinical mastitis, 2 samples (5%) were clinical mastitis and 1 sample (2,5%) were normal. Staining showed 7 colonies were basil. The identification result on MCA, EMB, TSI, IMViC, sugars broth and urea agar showed that 2 colonies were Klebsiella pneumoniae, 2 colonies were Klebsiella oxytoca, and 1 colony was Escherichia coli found on the subclinical mastitis milk. Besides that, 1 colony was identified as Citrobacter freundii found on normal milk.